The estimation of the factors that determine the productivity of the public universities of the Southern region of Mexico - Reyes Fong, Teodoro (2019)
Mexican public universities have placed special interest in achieving their objectives eciently; theabove, becomes more relevant if the university is considered as an organization whose goals are non-nancial, so, it requires public resources to achieve its goals. The objective of this study is to estimatethe factors that determine the productivity of public universities in the Southern region of Mexicoduring the period 2007 to 2017; for this,were used the inputs and outputs that make up the substantivefunctions of the universities, in the estimation the technique Data Envelopment Analysiswas usedto determine theMalmquist Productivity Index of 8 public universities. The ndingswere that in thegroup of universities analyzed there is an increase in productivity, and that this is due to the improvementin the productive processes; likewise, universities act according to the principle of eciency. Asconclusions we can point out, that the estimations by means of the Malmquist productivity Indexallow to know the determining factors in the productivity of the studied units, and the size of theuniversities represents a fundamental element in the positive changes of the university productivity